Pregnancy Promotes Maternal Hippocampal Neurogenesis in Guinea Pigs - Lily Wan; Tian Tu; Qi-Lei Zhang; Juan Jiang; Xiao-Xin Yan (Neural Plasticity)
Adult neurogenesis in the hippocampal dentate gyrus (DG) modulates cognition and behavior in mammals, while motherhood is associated with cognitive and behavioral changes essential for the care of the young. In mice and rats, hippocampal neurogenesis is reported to be reduced or unchanged during pregnancy, with few data available from other species. In guinea pigs, pregnancy lasts ~9 weeks; we set to explore if hippocampal neurogenesis is altered in these animals, relative to gestational stages. Time-pregnant primigravidas (3-5 months old) and age-matched nonpregnant females were examined, with neurogenic potential evaluated via immunolabeling of Ki67, Sp8, doublecortin (DCX), and neuron-specific nuclear antigen (NeuN) combined with bromodeoxyuridine (BrdU) birth-dating. Relative to control, subgranular Ki67, Sp8, and DCX-immunoreactive (+) cells tended to increase from early gestation to postpartum and peaked at the late gestational stage. In BrdU pulse-chasing experiments in nonpregnant females surviving for different time points (2-120 days), BrdU+ cells in the DG colocalized with DCX partially from 2 to 42 days (most frequently at 14-30 days) and with NeuN increasingly from 14 to 120 days. In pregnant females that received BrdU at early, middle, and late gestational stages and survived for 42 days, the density of BrdU+ cells in the DG was mostly high in the late gestational group. The rates of BrdU/DCX and BrdU/NeuN colocalization were similar among these groups and comparable to those among the corresponding control group. Together, the findings suggest that pregnancy promotes maternal hippocampal neurogenesis in guinea pigs, at least among primigravidas.